UNIVERSIDADE E MODIFICAÇÃO ORGANIZACIONAL - DO MODELO BUROCRÁTICO À ORGANIZAÇÃO INTENSIVA DE CONHECIMENTO - Adelcio Machado dos Santos (Revista Gestão Universitária na América Latina, 2012)
This article focus on upper education, specifically at universities, now inserted in a context of globalization, searching to understand how these organizations, which rose in the Middle Age, going through transformations of modernity and of the Illuminism, have reached the XXI Century, facing challenges of their sustainability, from values, mission and cultural tradition, kept throughout the centuries. According to this vision, some authors defend that one of the elements to understand the process of change through which the society goes is the progressive raise of the dependence of the countries, of governments, of companies and of individuals in relation to knowledge. Nations and individuals perceive their condition of interdependence towards each other and the central role knowledge performs, being necessary for this that a new vision concerning the knowledge intensive organization be given. Thus, this showing of how organizations share knowledge and how this is made easier by the quick spreading through the media and cyberspace, a brief history of the university will be presented, so that one can understand which way these organizations behave with technological and structural changes of new days, when it will be possible to observe that the mentioned organizational change can assure sustainability in the conjuncture of long-lasting transformations. In order to reach these objectives, the methodology of bibliographical research will be used. In this research it was evident that university is a complex organization, where bureaucracy in certain moments is an obstacle to growth, being necessary for this that managers and/or administrators use all their organizational knowledge to run it, because of this, the importance of organizational changing in administration.